Sport development in South Africa : skill development or talent identification? An evaluation of skill development initiatives in Tshwane for athletes aged 7 to 18 years - Van der Klashorst, Engela (University of Pretoria, 2019)
Dissertation (MA)--University of Pretoria, 2018.